Development E-Archive Web System for District Office Letters Management - Alfiah, Fifit; Setiadi, Ade; Amalia, Andiena (Journal Collabits, 2024)
Every company, business entity, or agency, both private and government, requires archiving activities because they are very necessary, given the importance of the role of archives. Therefore, to carry out archiving tasks properly, there must be improvements and optimal improvements so that they can function properly and achieve the goals that have been set. set. The availability of complete and accurate data and information will become a fundamental requirement in any organization, private or government. Understanding the significance of filing in terms of assisting leaders in making decisions or dealing with problems at the Larangan District Office in Tangerang City. Especially in the general section, where filing and processing document activities are still done traditionally, work takes a long time. The process of selecting data and reporting is difficult to manage because the data is distributed in multiple locations and various forms. Observation, interviews, and a literature review were used following the PIECES method. After analyzing, the authors propose a website-based Electronic Archive system for archiving incoming and outgoing mail, which also serves as a data storage area. As a result, the existence of a new system can reduce errors during data processing, and make the search process faster, and the reports generated follow the existing data